Leadership : the inner side of greatness : a philosophy for leaders - Koestenbaum, Peter, 1928- (Jossey-Bass business & management series., 2002)
It has been more than a decade since the first edition of Peter Koestenbaum's landmark book Leadership: The Inner Side of Greatness was published. Since that time world events have caused a dramatic shift in how we think about our lives and our work. Now we grapple with the fundamental questions. How can we live a courageous life and manage anxiety? Is it possible to reach greater heights of ethics and responsibility? Peter Koestenbaum, the preeminent business philosopher, has been a trusted mentor to business leaders worldwide.